Menelusuri Karya dan Karsa Manthou’s Sebagai Seniman dan Pencipta Campursari - JOKO TRI LAKSONO (Institut Seni Indonesia Yogyakarta, 2008)
Manthous as Campursari Musician and Composer. The study reveals that in his early age Manthous wasnurtured in a highly disciplined environment, and he had a strong determination to become a reliable fi gure in theart-world. Before composing Campursari Manthous had dealt with Pop Krontjong which was well-recognizedworldwide. In addition, Manthou’s also served as a recording programmer in several well-known recording studios.Through years Manthous has developed his musical skills as music player, singer, composer and artist manager. Hiscompositions contain simple lyric, diction, and rhyme. They have been composed in accordance to his personalmoods, marketing strategies and orders. By composing Campursari, he expects all groups of people, especially theyoung generation, can accept and enjoy Javanese musical performance (karawitan) in different form